Akuntablitas Kinerja dalam Peningkatan Layanan di Perumda Air Minum Kota Makassar - Mitha; Ilham Z Salle; Sahabuddin (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to understand accountability in improving services at the Regional Drinking Water Company of Makassar City. The analysis method used is qualitative descriptive analysis. In this research, the author utilizes both primary and secondary data. Data collection techniques involve direct interviews with relevant parties at the Regional Drinking Water Company of Makassar City. The results of the study indicate that the company's accountability is reflected through six main supporting indicators, namely: the moral quality of employees is quite good, the legitimacy of policies is maintained through openness and consistency, sensitivity to complaints and customer needs that need to be continuously improved, adequate information openness that can still be developed participatively, and efficient utilization of resources in accordance with expertise to support service quality. Overall, the company demonstrates a strong commitment to implementing accountability principles, although there is still room for strengthening, especially in the aspects of service and public responsiveness.